Requirements Of Central Control And Supervision On Islamic Banking Industries - Marai.A.D.Abdalla; Muhammad Ridhwan Bin Ab. Aziz; Fuadah Binti Johari (Australian Society For Commerce Industry & Engineering, 2024)
This study deals with the nature of Islamic banks and their features, and requirements of these features in terms of control tools and methods appropriate with the particularity of their business and their relation with the traditional central bank. The study aims also to be acquainted with the extent of appropriateness of the traditional control tools and the particularity of the Islamic banking work. The study arrived at a set of requirements which are necessary to adapt the control tools of the traditional central bank with the particularity of the Islamic banking work. The study set also a concept of a control framework supporting the Islamic banking work and regulating the relation of the Islamic banks with the traditional central bank in a manner securing for them an appropriate investment environment free from control and supervision hindrances.